Muslimah and Environmentalism - Anita Dewi Moelyaningrum; Dewi Rokhmah; Ninna Rokhmawati (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2018)
Environmentalism is the understanding and attitude to preserve the environment that should be owned by all Muslims because it is part of the teachings of religion. Environmental sustainability can be achieved with the behavior of people who paid attention to the environment well. The results of this study indicated that many respondents who didn’t know the verses of environmental sustainability so that it has not motivated them to act to preserve sustainability. Need synergy of government and society in introducing the verses of environmental sustainability through formal education-informal so that can be given motivation of society to behave to preserve environment.